PERSONNEL DEVELOPMENT MANAGEMENT OF BUSINESS ENTITIES THROUGH THE PRISM OF CORPORATE CULTURE - Зелінська, Галина Олексіївна; Андрусів, Уляна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article covers issues related to the management of the corporate culture of the enterprise and staff development. Problems of effective management and administration of the enterprise depend not only on economic, social, environmental factors. They directly depend on the culturological factor. Corporate culture is a component of corporate policy. It is determined that one of the main tasks of modern enterprise management is the development of corporate culture and its components. It was found that the development of corporate culture is closely related to increasing attention to personnel management and creating a psychological climate, focusing on dialogue between management and employees. It is determined that when forming the conceptual foundations of corporate culture development management should take into account not only the psychological and historical features of its formation, but also the market component - the ability to self-organization. The latter becomes a catalyst for the effective use of potential staff. It has been found that effective corporate culture management involves determining the willingness of management to change. Emphasis is placed on the choice of enterprise management strategy. Depending on the formation of the company’s mission will depend on the approach to corporate culture management. The study of factors influencing the formation of corporate culture of the enterprise proves that the level of macrofactors for all enterprises is the same, mesofactors and microfactors have features at the level of a particular enterprise and they form a variety of corporate cultures. It is proved that the strengthening of competition in the market enhances the action of micro and mesofactors, and therefore their manifestation requires new, effective methods and ways of working with staff. It was found that corporate culture is also a question of staff motivation, leadership style, the influence of the leader’s personality, etc. It covers most of the spiritual and material life of the team. It is determined that the existence of a democratic society actualizes the problem of introduction of humanitarian norms of interconnection in the organization of the system of management and subordination of administrative relations to the requirements of the humanitarian paradigm. It is complicated by the fact that the theoretical and methodological understanding of the state of culture has not yet been properly embodied in the organization of the enterprise management system. Emphasis is placed on the fact that the practice of enterprise management often demonstrates either underestimation of the cultural component of development, or attempts to solve complex problems using borrowed foreign methods. As a result - the lack of culture, the lack of its priority in the team is one of the reasons for slowing down the process of effective reforms in the enterprise. It is determined that new approaches to the system organization of enterprise management are largely determined by changes in the motivation of both managers and traditional specialists (specialists). They are considered in close connection with the increasing role of corporate culture in the management process - a tool to increase the social responsibility of staff for the effectiveness of the production process (provision of services). In this sense, the role of corporate culture is growing as a tool to motivate the management system, which aims to maintain employees’ confidence that they are the only team capable of solving complex problems.